Skin Lesion using SVM - Dr. S. Srinivasan, S. Prasanna Bharathi, G. Chamundeeswari (International Journal of Advanced Science and Technology, 2020)
Skin disease is one of the most vulnerable diseases in the world right now. A skin lesion is part of the skin which, similar to the skin surrounding itself, has an irregular growth or appearance. The main and secondary types of skin lesions are identified. Primary skin injuries are irregular skin disorders that develop at conception or that arise over the life of a human. Secondary lesions of the skin develop from original skin lesions that become disturbed or distorted. For example, the resultant lesion, a crust, is still a secondary skin lesion if someone bites a mole before it bleeds. In this paper, we proposed deep learning techniques to predict a classification area using Support vector machine and HAM1000 dataset to for an analysis report.